Enunciação e gramática : o ensino dos modos verbais da língua portuguesa sob a perspectiva da teoria enunciativa de Émile Benveniste - Marchett, Nathaline Bachi (My University, 2022)
This thesis aims to propose principles for teaching verbal modes of the Portuguese language in the Final Years of Elementary School, guided by Émile Benveniste's Theory of Enunciation. For this purpose, initially, a resumption is made on the origin of grammar in the West, as well as the beginnings of the grammatization of the Portuguese language, intending to understand the bases of this ancient discipline that, many times, underlies the work of the language teacher, as well as the elaboration of textbooks that the schools adopt. Next, we investigate the approach to verbal modes of the Portuguese language in a few grammar books that contemplate different theoretical perspectives - Cunha and Cintra (2016); Bechara (2019); Perini (2016); and Neves (2011) -, focusing on the notion of verb and the inflections that constitute the verbal paradigm, namely: number, person, tense and, mainly, mode, given that this is the object of this research. Furthermore, we present an overview of how Benveniste's studies were received in Brazil, highlighting the directions taken by such studies - among them, their grammar application - to, finally, revisit the notions of enunciation, person, subjectivity, and time, fundamental for the understanding of verbal paradigms, in the volumes of Problems in General Linguistics I and II (2005; 1989), by Émile Benveniste. Finally, to contribute to the teaching of the verbal modes of the Portuguese language, two textbooks used in the sixth year of Elementary School are analyzed, which make up the most distributed collections in Brazilian schools (first and second placings), according to data released by the National Book and Teaching Material Program (PNLD/2020). Based on this analysis, in which textbooks are used as an orientation resource in terms of teaching Basic Education, principles of Benveniste's Enunciative Theory are proposed for the teaching of verbal modes of the Portuguese language in the Final Years of Elementary School, demonstrating that this theory can be the starting point for teaching-focused not only on forms but also on the use of language. [resumo fornecido pelo autor]
Esta dissertação tem por objetivo propor princípios para o ensino dos modos verbais da língua portuguesa nos Anos Finais do Ensino Fundamental, pautados pela Teoria da Enunciação de Émile Benveniste. Para isso, faz-se, inicialmente, uma retomada da origem da gramática no Ocidente, bem como dos primórdios da gramatização da língua portuguesa, tencionando-se compreender as bases dessa disciplina milenar que, muitas vezes, fundamenta o trabalho do professor de língua, bem como a elaboração de livros didáticos que chegam à sala de aula. Na sequência, investiga-se a abordagem dos modos verbais da língua portuguesa em alguns compêndios gramaticais que contemplam diferentes perspectivas teóricas ? Cunha e Cintra (2016); Bechara (2019); Perini (2016); e Neves (2011) -, enfocando a noção de verbo e as flexões que constituem o paradigma verbal, quais sejam: número, pessoa, tempo e, principalmente, modo, dado ser este o objeto desta pesquisa. Ademais, apresenta-se um panorama da recepção dos estudos benvenistianos no Brasil, salientando-se as direções tomadas por tais estudos - dentre elas, sua aplicação à gramática -, para, enfim, revisitar-se, nos volumes de Problemas de linguística geral I e II (2005; 1989), de Émile Benveniste, as noções de enunciação, pessoa, subjetividade e tempo, basilares para a compreensão dos paradigmas verbais. Por fim, visando-se contribuir para o ensino dos modos verbais da língua portuguesa, são analisados dois livros didáticos de sexto ano do Ensino Fundamental que compõem as coleções mais distribuídas nas escolas brasileiras (primeiro e segundo lugares), segundo dados divulgados pelo Programa Nacional do Livro e do Material Didático (PNLD/2020). A partir dessa análise, em que se busca, nos livros didáticos, um recurso orientativo no que diz respeito ao ensino na Educação Básica, são propostos princípios da Teoria Enunciativa de Benveniste para o ensino dos modos verbais da língua portuguesa nos Anos Finais do Ensino Fundamental, demonstrando que essa teoria pode ser o ponto de partida para um ensino voltado não somente às formas, mas também ao uso da língua. [resumo fornecido pelo autor]
Keywords: Língua portuguesa (Ensino fundamental) - Gramática - Estudo e ensino; Linguística estrutural; Gramática comparada e geral; Análise do discurso; Benveniste, Émile, 1902-1976; Portuguese Language (Elementary School) - Grammar - Study and teaching; Structural linguistics; Grammar, Comparative and general; Discourse analysis